2016
DOI: 10.1177/1741143214564679
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the self-assessment of governing body performance in colleges and schools in England

Abstract: This study considers the rhetoric and practice of self-assessment by governing bodies of schools and colleges. The context expects governing bodies to reflect on their performance and this is supported by theoretical approaches to self-assessment of 'boards'. However, there are both general notes of caution and interview evidence of the complexities and limitations of selfassessment by governing bodies. The article includes advice on the basic conditions necessary for undertaking self-assessment by school and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In the absence of interviews with governors it is not possible to identify what effect this is having on governing bodies, but it is argued that this is worthy of further study – particularly in terms of governor abilities to self-assess. Realistic governor self-assessment is very difficult to achieve, as a recent project carried out by Hill and James (2014) reflected . It is therefore reasonable to assume that to a certain extent governors look to inspection reports and head teachers for confirmation of validity in their role.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of interviews with governors it is not possible to identify what effect this is having on governing bodies, but it is argued that this is worthy of further study – particularly in terms of governor abilities to self-assess. Realistic governor self-assessment is very difficult to achieve, as a recent project carried out by Hill and James (2014) reflected . It is therefore reasonable to assume that to a certain extent governors look to inspection reports and head teachers for confirmation of validity in their role.…”
Section: Resultsmentioning
confidence: 99%
“…This combined combined with the normative approaches of head teachers and inspectors, leads to a fundamental undermining of the effectiveness of an education policy which has put 300,000 people in charge of schools many of whom are apparently from the 'wrong sort of background.' It also creates issues in terms of diversity, as reflected by a recent study by The University of Bath (James, 2014).…”
Section: Some Of Our Governors Are Local Yes But Others Don't Reallymentioning
confidence: 99%
See 1 more Smart Citation
“…To clarify the statement, many studies have found and concluded that principals are key people who play an important role in school progress [8], [10]. Headmasters become the benchmarks of school success and failure.…”
Section: Introductionmentioning
confidence: 99%